2021
DOI: 10.3389/fchem.2021.677821
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Inorganic Thermoelectric Nanomaterials: Electrical Properties, Interfacial Chemistry Engineering, and Devices

Abstract: Though solar cells are one of the promising technologies to address the energy crisis, this technology is still far from commercialization. Thermoelectric materials offer a novel opportunity to convert energy between thermal and electrical aspects, which show the feasibility to improve the performance of solar cells via heat management and light harvesting. Polymer–inorganic thermoelectric nanocomposites consisting of inorganic nanomaterials and functional organic polymers represent one kind of advanced hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Nanomaterials are tiny particles with size distribution less than 100 nm. In the last decades, various types of nanomaterials have attracted the attention of many researchers in photocatalysis (Pan et al, 2021), electrocatalysis (Zhang et al, 2021a), photoelectrocatalysis (Hu et al, 2020;Zhao et al, 2020;Huang et al, 2021), solar utilization (Jiang et al, 2020), heat management (Zhang et al, 2021b) and other fields because of their unique properties (Wang et al, 2019;He et al, 2020). Among the numerous materials, Au represents one well-studied type (Xu et al, 2016) with tunable shape (Zhu et al, 2015), structure (Ma et al, 2015), and composition (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are tiny particles with size distribution less than 100 nm. In the last decades, various types of nanomaterials have attracted the attention of many researchers in photocatalysis (Pan et al, 2021), electrocatalysis (Zhang et al, 2021a), photoelectrocatalysis (Hu et al, 2020;Zhao et al, 2020;Huang et al, 2021), solar utilization (Jiang et al, 2020), heat management (Zhang et al, 2021b) and other fields because of their unique properties (Wang et al, 2019;He et al, 2020). Among the numerous materials, Au represents one well-studied type (Xu et al, 2016) with tunable shape (Zhu et al, 2015), structure (Ma et al, 2015), and composition (Jiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…to rationally design materials with high figures of merit (zT = σS 2 T κ −1 ). [8][9][10] In particular, hybrid materials composed of tellurium (Te) nanowires (NWs) embedded in poly (3,4-ethylenedioxythiophen e):poly(styrenesulfonate) (PEDOT:PSS) have been prominently studied after Yee et al reported that their TE performance could be tuned by varying the length of the NWs and modulating the amount of PEDOT:PSS incorporated into the system. In this way, they were able to achieve a power factor (PF = σS 2 ) close to 100 µW m −1 K −1 .…”
Section: Thermoelectric (Te) Materials That Can Directly Interconvert...mentioning
confidence: 99%
“…An effort to design environment-friendly thermoelectric materials has led to the discovery of Pb-and Te-free Cu-and Sn-based chalcogenides, skutterudites, chalcopyrites, carbon based materials, and so forth. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Notably, the thermoelectric figure of merit has reached a maximum value beyond two in recent years for single-crystal SnSe at 1000 K, which has been considered the most promising thermoelectric material to date. [30][31][32] The spiral plot in Fig.…”
Section: Strategiesmentioning
confidence: 99%